MODES DE PARTICIPATION DES JEUNES AU JEU POLITIQUE EN CÔTE D’IVOIRE : L’EXEMPLE DES ESPACES DE DISCUSSIONS DE RUE - N’Goran Koffi Parfait; Silue N’Tchabétien Oumar (European Scientific Journal, ESJ, 2012)
Since some years, the Ivorian youths show upsurge of interest in the country’s political game and play a pivotal role in that game through street discussion spaces. They seem to operate out in street discussion spaces that are thought to be on the periphery of the more authorized and official political sphere, but their interaction with political parties and political organizations has turned them into significant political actors. Street discussion spaces are alternative spaces for youth to integrate the political sphere that used to be a closed-space; a space they were excluded from by their elders until the nineties. They now contribute to the ‘‘cast’’ of new political figureheads. This new generation of actors uses ICT devices on a daily basis to diffuse political ideologies and organize communal actions as well. Since 2002, since the debut of the ongoing military and political crisis, street discussion spaces have not stopped growing; this fact is an expression of youth’s desire to participate in the political debate, to communicate their hopes and expectations. Actually, these spaces are also “spaces of resistance”, “arenas” where youth groups in quest for new political and cultural identities and a good position in the society, confront one another.